USING DIFFERENT PERCENT FROM CONCENTRATE AND ROUGHAGE IN FATTNING HOLSTEIN FRISIAN CALVE - & et al., Alkudsi (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2016)
The experiment was carried out at the Animal Farm / Department of Animal Resources/ College of Agriculture, University of Baghdad, to study the effect of using different percentage of concentrate to roughage in fattening calves .Two equal groups of Holstein Frisian calves, with age about eight months and at average weight of 228.8±21.2&227.8±9.12 kg /hd respectively. The calves placed in two neighboring barn. The animals fed by 3% live weight in the first two weeks then the ratio was raised to 4% of the live weight to the end the experiment. The animal’s weights and some body measurements were recorded at the beginning of the experiment, then after two weeks until the end of experiment (body wt., Chest circumference, withers height, abdominal circumference, body length). The average daily gain in the first group was 0.957 kg/hd while the average daily gain was 0.970kg/hd in the second group. In the end of experiment the weight of calves in the first group were 1428 kg / Group, while the weight in the second group was 1430 kg / group.. The amount of roughage consumption in the first and second group 1594.4 and 1070.6 kg, While the amount of concentrate consumer in the first group 1064kg and the second group was 1549.8kg. It can be concluded from this study that the use of alfalfa hay to feed concentrate diet at the level of 60 : 40 from daily feeding in the fattening Holstein Frisian calves at the age of eight months is the best because it reduces the costs and to achieve the desired purpose.